Optical demonstration of quantum fault-tolerant threshold - Kai Sun; Ze-Yan Hao; Yan Wang; Jia-Kun Li; Xiao-Ye Xu; Jin-Shi Xu; Yong-Jian Han; Chuan-Feng Li; Guang-Can Guo (Light: Science & Applications, 2022)
We observe the error rate threshold of quantum fault-tolerant computation by using optical spatial modes of two entangled photons to encode logical qubits.